PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Riska, Riska; Raza, Hendra; Zulfa, Andria (J-MIND (Jurnal Manajemen Indonesia), 2020)
ABSTRACTThis study aims to examine the effect of profitability, liquidity and leverage on firm value with dividend policy as a moderating variable on Manufacturing Companies on the Stock Exchange during the 2014-2018 period. The number of samples in this study are 28 Manufacturing Companies on the Stock Exchange that provide regular dividends during the 2014-2018 period. The type of data used is secondary data in the form of panel data obtained from the company's Annual Report. Data analysis method used is Panel Data Regression. The results of this study found that profitability, leverage and dividend policy had a positive and significant effect on firm value, but liquidity had no significant effect on firm value. The moderating effect proves that the dividend policy is able to moderate the effect of profitability, liquidity and leverage on the value of the company, where the dividend policy belongs to the type of variable Quacy Moderator.Keywords : Profitability, Liquidity, Leverage, Dividend Policy and Company Value